Improving Learning Outcomes through Innovative Pedagogical Approaches in Modern Education - Khadijah, Ifah; Nurhamidah, Nunung; Mulyani, Lina; Amanah, Siti Nur; Sukmanawati, Nina (Universitas Pahlawan Tuanku Tambusai, 2025)
This study evaluates the effectiveness of innovative teaching methods in enhancing student learning outcomes at SMAN 1 Sindangkasih Ciamis. Driven by the need to modernise conventional teaching approaches, the research employs a mixed-methods design, incorporating surveys, interviews, and classroom observations with grade X and XI students and teachers. Findings indicate that project-based learning and information technology integration enhance both academic performance and student engagement. Thematic analysis further highlights improvements in motivation and social skills. However, challenges such as insufficient teacher training and inadequate facilities persist. To address these issues, the study recommends on going professional development, strengthened collaboration with parents, and curriculum adjustments to align with modern educational demands.